Pharmacists in antibiotic resistance prevention education at Makassar Mandai Market - Andi Maulana Kamri; Rachmat Kosman; Asmarani Pujawanti; Ratu Ananda; Shinta Ferawati; Nurbaeti Asnawi; Besse Ati; Khaerana Majid; Safitri Ayu; Indra Indra; Andi Hasriyana; Nabila Said (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Antibiotics are drugs that are used to treat bacterial infections. The thing that must be considered by pharmacists is the use of antibiotics without a doctor's prescription where if used incorrectly it will cause the problem of antibiotic resistance in a population. Therefore, efforts are needed to increase public basic knowledge of current treatment by providing drug information or education to the community. This activity was carried out by gathering 50 respondents to conduct interviews (pre-test and post-test) and public education on the theme of antibiotic resistance. Based on the results obtained, the community's understanding in terms of the use of antibiotics is increasing regarding the rules for use and when to use antibiotics. The public understands for free buying antibiotics without a doctor's prescription is a bad choice and there are people who based knowledge on antibiotic resistance, antimicrobial resistance, or drug resistance addition. Public understanding of the use of antibiotics is still low. This was proven when people bought antibiotics freely anywhere.